The role of social proximity in professional CEO appointments: Evidence from caste/religion-based hiring of CEOs in India - Damaraju, Naga Lakshmi; Makhija, Anil K. (Strategic Management Journal, 2018)
[Research summary: The role of homophily in CEO appointments at the largest corporations is an important subject in corporate governance. This subject is particularly important in a country like India where a multitude of religions, castes, and communities form its social fabric. We test for the role of homophily in professional CEO appointments in India by empirically examining the preference for same caste/religion CEOs by the largest firms. Using a unique dataset, assembled by detailed identification of castes/religions from family names and counterfactuals obtained through the Coarsened Exact Matching technique, we find that caste/religion plays a crucial role in CEO selection as a source of information (positive discrimination). The evidence is not consistent with its use to pursue taste-based preferences (negative discrimination). Managerial summary: We test for the role of homophily in the appointments of CEOs in India by empirically examining the preference for same caste/religion CEOs by the largest firms. We find that caste/religion plays an important role in CEO selection, i.e., as a form of information or "positive discrimination." The evidence is not consistent with its use to pursue taste-based preferences or "negative discrimination."]